Antibiotic Resistance Profiling of Escherichia coli O157:H7 from Guinea fowl and Chicken in Ibadan North Local Government area, Nigeria (2017)
Escherichia coli Ol 57 is a major zoonotic disease of thè poultry industry. 315 cloacae samples (177 chickens and 138 guinea fowls) were screened for enterohaemorrhagic E. coli (EHEC 0157). The samples were pre-enriched with tryptic soy broth, incubated over- night at 37°C for 18 hours, sub-cultured on MacConkey agar and incubated at 37°C for 24 hours. Rose pink colonies on MacConkey agar (putative E. coli) were selected for bio- chemical test. The susceptibility of identified E. coli isolates to antimicrobial agents was determined by thè standard Kirby-Bauer disk diffusion method on Mueller-Hinton agar. Confirmed E. coli were sub-cultured on Sorbitol MacConkey agar piate (SMAC) and incubated at 37°C for 24hours. Colourless or pale colonies (non-sorbitolfermenters) were further tested. Isolates that produced colourless colonies and agglutinatimi with E. coli 0157 latex test were tested with E. coli HI antiserum by a slide agglutination test as well as other identified E. coli isolates irrespective of their sorbitol fermentatimi reactions were identified serologically using a latex agglutination test kit. Of thè 315 samples, 9.5% were positive for EHEC Ol 57 including 7.3% and 12.3% of thè chickens and thè guinea fowls, respectively. The differences in thè two species were not statistica!ly (P<0.05) significant The resistance of thè EHEC 0157 to antim icrobials were; amoxicillin/clavulanic acid 66.67%, nitrofurantoin 60.00%, gentamicin 56.67%, trimethoprim/sulphamethoxazole 50.00%, tet- racycline 50.00%, pefloxacin43.33%, amoxicillin 33.33 %, ciprofloxacin 33.33 %,ofloxacin 30.00%, and ceftriaxone 20.00%. E. coli OJ57:H7 isolated from guinea fowls were all susceptible to amoxicillin and ciprofloxacin while EHEC 0157:H7 from chickens showed 100% resistance to tetracycline and pefloxacin. The presence of virulent multidrug resistali E. coli 0157 strains in thè faeces of guinea fowls and chickens showed thè dangers that handlers and consumers are exposed and thè implications of disseminatimi of thè pathogens to thè environment through faecal shedding.